Frequency Domain Analysis of Tractor Tyre Enveloping Properties - Stojic, Boris (International Journal of Engineering and Management Sciences, 2019)
Main source of vibration excitation for off-road vehicles are ground profile undulations. Most unprepared terrains are characterized by wavelength of unevenness that is of the order of magnitude of the contact length between tire and ground, so that, due to its shape and elasticity, tire actually behaves as geometric low-pass filter transforming real road profile geometry into effective vehicle vibration excitation. Since this effective profile represents real vehicle excitation, it is of interest to study this filtering behaviour in more depth. In this work, investigation of this kind of tire response has been studied for agricultural tractor tire rolling quasistatically over singular road obstacle. Frequency analysis of road excitation and tyre response was carried out in order to obtain their spectra and frequency response function magnitude of the tyre as filter was obtained by dividing input by output spectra. Final assessment of frequency response function magnitude was obtained by averaging instances obtained for different dimensions of input obstacles.